Proteasomal dysfunction induced by 4-hydroxy-2,3-trans-nonenal, an end-product of lipid peroxidation: A mechanism contributing to neurodegeneration? - Hyun, D.-H. (2013)
10.1046/j.1471-4159.2002.01125.x